2006
DOI: 10.1128/jb.00557-06
|View full text |Cite
|
Sign up to set email alerts
|

Essential Role of Flavohemoglobin in Long-Term Anaerobic Survival of Bacillus subtilis

Abstract: A Bacillus subtilis culture incubated anaerobically in nitrate-containing medium lost viability during the first 3 days but recovered thereafter. A flavohemoglobin mutant showed very poor survival under these conditions unless the cells were prevented from carrying out nitrate respiration.Bacillus subtilis responds to nutritional starvation by forming dormant spores, which ensures a long-lasting capability to resume growth upon encountering favorable conditions. B. subtilis strain 168 grows under anaerobic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Although the anaerobic NO reductase activity of FHb remains controversial due to its significantly lower catalytic rate compared to its aerobic NOD activity (Kim et al, 1999), anaerobic protection against NO by FHb has been noted in Salmonella typhimurium (Crawford and Goldberg, 1998), E. coli (Gardner et al, 1998b), and S. cerevisiae (Liu et al, 2000). In addition, FHbs of Staphylococcus aureus and B. subtilis have been shown to protect their cells from NO stress only under O 2 -limiting conditions (Nakano, 2006;Gonçalves et al, 2006). These results emphasize the possible anaerobic roles of FHb and suggest that a possible anaerobic NO metabolism involving FHb may exist.…”
Section: Discussionmentioning
confidence: 97%
“…Although the anaerobic NO reductase activity of FHb remains controversial due to its significantly lower catalytic rate compared to its aerobic NOD activity (Kim et al, 1999), anaerobic protection against NO by FHb has been noted in Salmonella typhimurium (Crawford and Goldberg, 1998), E. coli (Gardner et al, 1998b), and S. cerevisiae (Liu et al, 2000). In addition, FHbs of Staphylococcus aureus and B. subtilis have been shown to protect their cells from NO stress only under O 2 -limiting conditions (Nakano, 2006;Gonçalves et al, 2006). These results emphasize the possible anaerobic roles of FHb and suggest that a possible anaerobic NO metabolism involving FHb may exist.…”
Section: Discussionmentioning
confidence: 97%
“…Other studies reveal unexpected roles for Hmp. A recent study (Nakano, 2006) has demonstrated that, in Bacillus subtilis, flavohaemoglobin Hmp has a role in long-term anaerobic survival: mutants defective in hmp exhibit poor survival when incubated anaerobically with nitrate unless nitrate respiration is prevented. Although this might be attributed to sensitivity to NO produced under these conditions, addition of NO-releasing NONOate compounds elicited no growth differences in the anaerobic growth of hmp and hmp + strains.…”
Section: Discussionmentioning
confidence: 99%
“…Flavohemoglobin detoxifies nitric oxide by anaerobically reducing it to N 2 O or by aerobically oxidizing it to nitrate. In B. subtilis, hmp has an essential role in long-term anaerobic survival only in nitratecontaining medium (22). Although C. glutamicum Hmp is not highly similar to either E. coli Hmp (32% identity) or B. subtilis Hmp (31% identity), C. glutamicum Hmp may play some protective role against possible oxidative stress during anaerobic growth with nitrate.…”
Section: Discussionmentioning
confidence: 99%